Racialization of the bilingual student in higher education: A case from the Peruvian Andes - Zavala, V. (Elsevier, 2011)
In the Andes, a phonological transference known as motoseo has acquired ideological weight. People think that bilingual speakers of Quechua and Spanish ‘confuse’ the vowels when speaking Spanish and that they are inferior to the ones who do not. In this article, I analyze the ideological agenda of the racialized verbal hygiene practice based on this phenomenon in two universities of the Peruvian Quechua-speaking context. I look at how students have internalized the ideology associated with the phenomenon and constantly discipline themselves to control it while speaking. In addition, I discuss how professors (most of whom are also speakers of Quechua) use this trait to otherize rural students and construct them as “they” as opposed to “us”. This ideology is so widespread in the area that it works to reproduce a profoundly unequal social order that is not questioned by most university professors nor by the students who are victims of it. In turn, it leads to low academic performance and a university experience that is often traumatic for students coming from rural areas.
Keywords: Racial difference; Cultural difference; https://purl.org/pe-repo/ocde/ford#5.04.03